Retranslation and paratext: Interlingual retranslations of the miserables in the Ottoman empire and their intralingual retranslations in modern Turkey - Gokduman, Umut Can; Karadag, Ayse Banu (LMS-MODERN LANG TEACHERS ASSOC, 2021)
The objective of this article is to analyze the interlingual and intralingual retranslations of Les Miserables (Sefiller in Turkish) in Turkey. With regard to interlingual retranslations during the Ottoman Empire and their intralingual retranslations in modern Turkey, the emphasis is on the different grounds for retranslation. To do this, we use paratexts of retranslations in question. This article aims to explore the imprints of literary actors in the publication of this work which entered into the Turkish territory in 1862, the year of its publication in France. This novel has since been retranslated several times, becoming one of the most retranslated works in Turkey. Given that the work has recognized different translation concepts such as intralingual and interlingual retranslations, the article explores these translation concepts in this work while highlighting the actors such as the translator, the owner of the publishing house and the critics. By looking for the why of the retranslation of Les Miserables in Turkey, this article puts forward various retranslations as well as the reasons for their existence in the Turkish context through the paratexts in order to form the panorama of the interlingual and intralingual retranslations of this masterpiece of Hugo.
Keywords: Les Miserables; Sefiller; interlingual retranslation; intralingual retranslation; paratext; TRANSLATION; (RE)TRANSLATION; Linguistics; Literature